1991
DOI: 10.1016/0042-6822(91)90750-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the glycoprotein gene of sonchus yellow net virus, a plant rhabdovirus

Abstract: The nucleotide sequence of the glycoprotein (G) gene of sonchus yellow net virus (SYNV), a plant rhabdovirus, was determined from viral genomic and mRNA cDNA clones. The G cistron is 2045 nucleotides (nt) long and the G protein mRNA open reading frame (ORF), as determined from the cDNA sequence, contains 1896 nt and encodes a protein of 632 amino acids. Immunoblots with antibodies elecited against the purified glycoprotein from virus particles reacted with a fusion protein produced in Escherichia coli, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 36 publications
(51 reference statements)
0
21
0
Order By: Relevance
“…By definition, viruses do not possess conserved P/MAMP-like features such as flagellin or chitin. However, structures such as, but not limited to, the virion (or capsid), viral ribonucleoprotein complexes, and viral-encoded glycoproteins embedded on the host-derived lipid membranes of plant rhabdoviruses (Goldberg et al, 1991;Jackson et al, 2005) are analogous to P/MAMPs. Importantly, these structures are conserved among members of related virus taxa.…”
Section: Future Prospects and Considerationsmentioning
confidence: 99%
“…By definition, viruses do not possess conserved P/MAMP-like features such as flagellin or chitin. However, structures such as, but not limited to, the virion (or capsid), viral ribonucleoprotein complexes, and viral-encoded glycoproteins embedded on the host-derived lipid membranes of plant rhabdoviruses (Goldberg et al, 1991;Jackson et al, 2005) are analogous to P/MAMPs. Importantly, these structures are conserved among members of related virus taxa.…”
Section: Future Prospects and Considerationsmentioning
confidence: 99%
“…For example, our attempts to express the sonchus yellow net virus (SYNV) glycoprotein by fusing RFP to its C terminus were unsuccessful. Despite the fact that SYNV glycoprotein contains a predicted N-terminal signal peptide (Goldberg et al, 1991), the correctly targeted fusion was that in which RFP was placed in frame ahead of the signal peptide . In a more detailed study, Simpson et al (2001) found that approximately 50% of human proteins, including those targeted to the ER or mitochondria, localized to the same subcellular locus when expressed as N-terminal fusions to CFP or C-terminal fusions to YFP (Pepperkok and Ellenberg, 2006).…”
Section: Beginning Middle or End-where To Fuse Your Afp?mentioning
confidence: 99%
“…The membrane fraction contains a glycoprotein (G) that protrudes from the surface of the virion (11) and an associated protein designated sc4 (46). The membrane fraction also contains an additional protein that is thought to be an analogue of the matrix protein (M) of the animal-infecting prototype rhabdovirus, Vesicular stomatitis virus (VSV) (16), which associates with the G protein and the nucleocapsid core during morphogenesis to stabilize the virus particle.…”
mentioning
confidence: 99%